2010
DOI: 10.1002/jor.21213
|View full text |Cite
|
Sign up to set email alerts
|

Gliding resistance of flexor tendon associated with carpal tunnel pressure: A biomechanical cadaver study

Abstract: ABSTRACT:The purpose of this study was to investigate the effect of carpal tunnel pressure on the gliding characteristics of flexor tendons within the carpal tunnel. Eight fresh human cadaver wrists and hands were used. A balloon was inserted into the carpal tunnel to elevate the pressure. The mean gliding resistance of the middle finger flexor digitorum superficialis tendon was measured with the following six conditions: (1) as a baseline, before balloon insertion; (2) balloon with 0 mmHg pressure; (3) 30 mmH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 39 publications
0
26
0
Order By: Relevance
“…1,2 It is typified by median nerve compression and results in various levels of disability. 3,4 Non-inflammatory subsynovial connective tissue (SSCT) fibrosis is present in patients with CTS, 5,6 even though the cause is still unclear. The SSCT fibrosis is also associated with elevated activity of transforming growth factor β1 (TGF-β1), which regulates fibroblast proliferation and reorganization of structural proteins linking the tissues in the extracellular matrix (ECM).…”
Section: Introductionmentioning
confidence: 99%
“…1,2 It is typified by median nerve compression and results in various levels of disability. 3,4 Non-inflammatory subsynovial connective tissue (SSCT) fibrosis is present in patients with CTS, 5,6 even though the cause is still unclear. The SSCT fibrosis is also associated with elevated activity of transforming growth factor β1 (TGF-β1), which regulates fibroblast proliferation and reorganization of structural proteins linking the tissues in the extracellular matrix (ECM).…”
Section: Introductionmentioning
confidence: 99%
“…CTS can be associated with repetitive manual activities, anatomic anomalies, autoimmune or hematologic disorders, arthritis, trauma, or neoplasms . Although etiology is unknown in most cases, studies have shown that symptoms and subsequent work‐related disabilities are created by increased pressure within the carpal tunnel, which causes compression and ischemia of the median nerve …”
Section: Introductionmentioning
confidence: 99%
“…Noninflammatory subsynovial connective tissue (SSCT) fibrosis is the most common histopathologic finding reported in patients with CTS . Moreover, studies of median nerve motion in idiopathic CTS patients and control subjects have clearly shown that nerve mobility is hampered in patients . SSCT fibrosis is also known to be associated with elevated activity of transforming growth factor (TGF)‐β1, which can upregulate fibroblast proliferation and activation.…”
Section: Introductionmentioning
confidence: 99%
“…Both increased pressure and high-velocity tendon motion result in increased GR, which suggests that high GR is related to CTS (Filius et al, 2014; Kociolek et al, 2015; Tat et al, 2013; Zhao et al, 2011). A good understanding of GR in the carpal tunnel is, therefore, important to better understand the pathology of CTS.…”
Section: Discussionmentioning
confidence: 99%
“…Wrist flexion and finger flexion, especially isolated flexion of a single finger (as may occur in typing or other repetitive work), are associated with high tendon gliding resistance (GR) and increased carpal tunnel pressure, which also increases GR (Ettema et al, 2004; Filius et al, 2014; Kociolek et al, 2015; Seradge et al, 1995; Zhao et al, 2011), but little work has been done to elucidate the mechanisms that contribute to tendon GR in the carpal tunnel.…”
Section: Introductionmentioning
confidence: 99%